Beyond eggs: Influence of deflavouring on the techno-functional properties of faba bean protein concentrate and potential as an innovative egg replacer in pound cake - Juliane Halm; Caner Caliskan; Laura Nyhan; Antonia Rosenberger; Aylin W. Sahin; Emanuele Zannini; Elke K. Arendt (Applied Food Research)
Utilising faba bean protein concentrate as an egg replacer in pound cake formulations offers a promising path for addressing dietary preferences and functional properties in baked goods. Further processing, like deflavouring, could significantly impact the techno-functional properties of the faba bean protein concentrate, ultimately leading to variations in cake texture and overall quality. The nutritional and techno-functional properties of faba bean protein concentrate original (FPC) and deflavoured (FPC(D)) were analysed and compared to a control whole egg powder (CEP). The ingredients were incorporated as egg substitutes in a pound cake formulation, and their impact on nutritional parameters, batter characteristics, and cake quality was assessed. Regarding the techno-functionality of the ingredients FPC(D) had a significantly lower protein solubility (78.4/ 51.9 %), foaming capacity (39.8/ 18.7 %), oil-holding capacity (114.2/ 59.0 %), emulsification and gelling ability, compared to the original product (FPC). However, the deflavouring process had a positive impact on foaming stability and water-holding capacity. The application of faba bean protein concentrate in a pound cake system demonstrated a correlation between its functional properties and the resulting cake quality. Compared to the control cake (2.21 mL/g), the specific volume was slightly decreased for the cakes containing FPC (2.00 mL/g) and FPC(D) (1.94 mL/g). Considering the texture of the cakes, the hardness parameter for the cakes containing CEP (9.31 N) and FPC (9.12 N) were comparable. In conclusion, incorporating faba bean protein concentrates yielded positive results, highlighting their potential as a favourable alternative to eggs. Further research is necessary to optimise utilisation and enhance nutritional and textural aspects and the appearance of the egg-replaced cakes.